Realization of fluence field modulated CT on a clinical TomoTherapy megavoltage CT system. (7th September 2015) - Szczykutowicz, Timothy P; Hermus, James; Geurts, Mark; Smilowitz, Jennifer
Abstract: The multi-leaf collimator (MLC) assembly present on TomoTherapy (Accuray, Madison WI) radiation therapy (RT) and mega voltage CT machines is well suited to perform fluence field modulated CT (FFMCT). In addition, there is a demand in the RT environment for FFMCT imaging techniques, specifically volume of interest (VOI) imaging. A clinical TomoTherapy machine was programmed to perform VOI. Four different size ROIs were placed at varying distances from isocenter. Projections intersecting the VOI received 'full dose' while those not intersecting the VOI received 30% of the dose (i.e. the incident fluence for non VOI projections was 30% of the incident fluence for projections intersecting the VOI). Additional scans without fluence field modulation were acquired at 'full' and 30% dose. The noise (pixel standard deviation) and mean CT number were measured inside the VOI region and compared between the three scans. Dose maps were generated using a dedicated TomoTherapy treatment planning dose calculator. The VOI-FFMCT technique produced an image noise 1.05, 1.00, 1.03, and 1.05 times higher than the 'full dose' scan for ROI sizes of 10 cm, 13 cm, 10 cm, and 6 cm respectively within the VOI region. The VOI-FFMCT technique required a total imaging dose equal to 0.61, 0.69, 0.60, and 0.50 times the 'full dose' acquisition dose for ROI sizes of 10 cm, 13 cm, 10 cm, and 6 cm respectively within the VOI region. Noise levels can be almost unchanged within clinically relevant VOIs sizes for RT applications while the integral imaging dose to the patient can be decreased, and/or the image quality in RT can be dramatically increased with no change in dose relative to non-FFMCT RT imaging. The ability to shift dose away from regions unimportant for clinical evaluation in order to improve image quality or reduce imaging dose has been demonstrated. This paper demonstrates that FFMCT can be performed using the MLC on a clinical TomoTherapy machine for the first time.